Nutrition and Enhanced Sports Performance Muscle Building, Endurance, and Strength - Bagchi, Debasis; Bagchi, Debasis; Nair, Sreejayan; Sen, Chandan K. (Elsevier Science, 2013)
Nutrition and Enhanced Sports Performance: Muscle Building, Endurance, and Strength provides a comprehensive overview to understanding the integrated impact of nutrition on performance. The book is divided into five main themes: An introductory overview of the role of nutrition in human health Various types of physical exercises, including cardiovascular training, resistance training, aerobic and anaerobic exercise, bioenergetics, and energy balance. This section also covers the nutritional requirements associated with various fitness programs, as well as exercise and nutritional requirements in special populations, including the pre-pubertal, young, elderly, and disabled. Sports and nutritional requirements. The molecular mechanisms involved in muscle building A thorough review of various food, minerals, supplements, phytochemicals, amino acids, transition metals, small molecules and other ergogenic agents that have been implicated in muscle building and human performance This book is an ideal resource for nutritionists, dietitians, exercise physiologists, health practitioners, researchers, students, athletes, trainers, and all those who wish to broaden their knowledge of nutrition and its role in human performance. Discusses the impact of nutrition, including food, minerals, vitamins, hormones, trace elements, etc., that can significantly attenuate/improve human performance and sports Addresses the molecular and cellular pathways involved in the physiology of muscle growth and the mechanisms by which nutrients affect muscle health, growth and maintenance Encompasses multiple forms of sports/performance and the salient contribution of appropriate nutrition on special populations, including nutritional guidelines and recommendations to athletes Strong focus on muscle building